Risco de quedas e níveis de fragilidade em idosos que fazem uso de ansiolíticos e/ou antidepressivos - Lamberti, Daciano Bastos (2017)
This research aimed to study the risk of falls and the levels of fragility in the elderly who use anxiolytics and / or antidepressants. This is a cross-sectional, analytical cross-sectional study involving elderly individuals aged 60 and over, both sexes, enrolled in the twelve Family Strategies of the city of Ijuí in the state of Rio Grande do Sul, which participated of the research "Evaluation of the use of antidepressant and / or anxiolytic as a risk factor for fragility, cognitive and functional decline of the elderly". Two peer groups were selected from the research database: the elderly who used antidepressants and/or anxiolytics, the "user" group (n = 107), and an elderly individual who was not randomly selected did not use these drugs (n = 114). Based on this selection, data were collected through the application at home, with a research protocol composed of a questionnaire for the sociodemographic characterization, the use of medication, and the instrument for the evaluation of balance and gait (Poma Brasil test). Fragility was evaluated according to the criteria proposed by Fried. It was observed that the sociodemographic characteristics, according to the levels of fragility, provided statistically significant difference between the users of antidepressants and / or fragile and non-fragile antianxiety agents for the age group; and among non-users of fragile and non-fragile antidepressants and / or anxiolytics for age and schooling. These data suggest that elderly older users as non-users of anxiolytics and / or antidepressants are in fragile condition. Regarding the variables of the Poma Brazil test, it was observed that when comparing elderly users and non-users regarding fragility as compared to fragile users and non-users and non-fragile users and non-users the results showed a better test score for non-users users and non-fragile users. These suggest that the use of antidepressants and / or anxiolytics interferes with the performance of the elderly's balance and consequently increases the risk for falls.